Polyhedral Bismuth Polycations Coordinating Gold(I) with Varied Hapticity in a Homoleptic Heavy-Metal Cluster - Mueller, Ulrike; Isaeva, Anna; Richter, Janine; Knies, Maximilian; Ruck, Michael (European Journal of Inorganic Chemistry, 2016)
Shiny black, air-sensitive crystals of [Au(Bi8)2](AlCl4)5were obtained from the reaction of AuCl, BiCl3, and bismuth in the ionic liquid [BMIm]Cl·4AlCl3(BMIm = 1-n-butyl-3-methylimidazolium) at 180 °C. [Au(Bi8)2](AlCl4)5crystallizes in the monoclinic space group P21/n. In the heavy-metal cluster [Au(Bi8)2]5+, two square-antiprismatic Bi82+polycations coordinate the gold(I) atom in η2- and η4-mode, respectively. Quantum chemical calculations demonstrate that both Bi82+polycations involve skeletal electrons for the donor bonding, which causes a widening of Bi–Bi distances compared with those in free Bi82+.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bismuth; Coordination modes; Gold; Ionic liquids; Polycations